Efficacy of MLN9708 (ixazomib) in experimental autoimmune myasthenia gravis and in anti-AChR producing primary thymic cell cultures from myasthenia gravis patients - Mané-Damas, Marina; Saxena, Abhishek; Nogales-Gadea, Gisela; Stevens, Jo; Vincken, Shannen; van Beek, Maarten; van den Hoogen, Nynke J.; Joosten, Elbert A. J.; Willcox, Nick; Duimel, Hans; Maessen, Jos G.; Molenaar, Peter C.; et al. (Frontiers in Immunology, 2025)
Proteasome inhibitors can eliminate malignant, alloreactive, or autoreactive plasma cells. These cells are key players in antibody-mediated autoimmune disorders and thus suitable therapeutic targets for these drugs. However, certain proteasome inhibitors cause toxic peripheral neuropathy in patients. Ixazomib (MLN9708, Ninlaro), an oral proteasome inhibitor, has a more favorable safety profile in multiple myeloma patients. Here we tested its efficacy in preventing and treating experimental autoimmune myasthenia gravis (EAMG). Female Lewis rats were treated with two subcutaneous doses of 0.35 mg/kg of ixazomib per week, starting either 4 weeks before or at disease onset; both substantially lowered final total IgG and rat acetylcholine receptor (AChR) autoantibody levels. Interestingly, two weekly doses of 0.20 mg/kg of ixazomib for the last 4 weeks did not reduce autoantibody levels. A single dose of 0.50 mg/kg was acutely toxic in rats. In cultures of thymic cells from early-onset myasthenia gravis (EOMG) patients, 30 nM ixazomib or higher almost completely eliminated plasma cells and halted their IgG and AChR antibody production. We conclude that proteasome inhibition with ixazomib effectively depletes plasma cells from MG patients in vitro and in a rat model in vivo. These results encourage further investigations into therapeutic plasma cell targeting for MG patients.